Numerical investigation of a two-bladed vertical-axis turbine operating in a confined channel. (December 2022) - Duarte, Leandro; Maguin, Nicolas; Dellinger, Guilhem; Dellinger, Nicolas; Vazquez, José
Highlights: Energy harvesting performance of a two-bladed vertical-axis turbine operating in a confined channel is investigated in a wide range of design parameters. Optimal values of tip-speed ratio for each solidity are identified, which turned out to be considerably higher compared to unconfined turbines. Average power coefficients as high as 6.29 can be achieved with a turbine design with solidity 0.30. Turbine performance can be further increased by reducing blade-channel gap. Abstract: The energy harvesting performance of a hydrokinetic turbine in a confined channel has been investigated through numerical simulations. It consists of a two-bladed vertical-axis turbine with a NACA0015 profile. Fluid dynamics are reproduced by a 2D numerical model solving the unsteady RANS equations through a finite volume approach in OpenFOAM-v6 . Following a numerical sensitivity analysis, the baseline model has been validated with respect to reference data for an unconfined turbine with similar design. The model has then been employed for assessing the influence of the main design parameters – namely blade-channel gap ε 0, solidity σ and tip-speed ratio λ – on the performance of the turbine. First, a parametric study on the plane λ × σ revealed that best performance is obtained at high solidity and low tip-speed ratios. In a range of solidities from 0.06 up to 0.48, the optimal value of tip-speed ratio – which is considerably higher when compared with unconfined turbines – is precisely identified. Finally, the effects of the blade-channel gap ε 0 on the performance of the turbine has been investigated as well. It has been found that ε 0 should be set as small as possible in order to maximise energy harvesting. Moreover, numerical results allowed for estimating a limit value of ε 0 > 9 over which the performance of a turbine operating in a confined channel should match that of an unconfined turbine.